Relationship of Farmer Group Roles with Corn Productivity in Karangreja Village, Cimanggu Sub-District, Cilacap Regency: A Spearman Rank Correlation Analysis - Safitri, Sulistiya Nur; Nuraini, Candra; Tedjaningsih, Tenten (University of Jember, 2024)
The role of farmer groups in rural areas is crucial to support the community in sustaining agricultural activities. This research aims to determine the role of farmer groups in enhancing corn productivity. The research method employed is a survey of corn farmer group members in Karangreja Village, Cimanggu Sub-District, Cilacap Regency, using proportional random sampling technique. The Likert Scale is utilized to assess the role of farmer groups, based on three sub-variables: learning classes, cooperation facilities and production units. To determine corn productivity and the relationship between the role of farmer groups and corn productivity, the Concordance Rank Kendall W and Rank Spearman Correlation tests are employed. The research findings indicate that the role of farmer groups falls within the 'involved' category. Corn productivity demonstrates an increase after participation in the farmer group. There is a significant simultaneous relationship between the role of farmer groups and corn productivity. Additionally, partial correlations are identified between the role of farmer groups in terms of learning classes, cooperation facilities, production units, and corn productivity.